Correlations of Neuropsychological and Metabolic Brain Changes in Parkinson's Disease and Other α-Synucleinopathies - Trošt, Maja; Perovnik, Matej; Pirtošek, Zvezdan (Frontiers in Neurology, 2019)
Cognitive impairment is a common feature of Parkinson’s disease (PD) as 40% of PD patients with normal cognition develop mild cognitive impairment within 6 years of diagnosis and 80% of all PD patients will develop dementia within 20 years. Early cognitive changes in PD patients present as dysexecutive syndrome, broadly characterized as a disruption of fronto-striatal dopamine network. Cognitive deficits in other domains (recognition memory, attention processes and visuospatial abilities) become apparent with progression of PD and development of dementia. Metabolic brain imaging with positron emission tomography and [18F]-fluorodeoxyglucose (FDG-PET) is a well-established diagnostic method in neurodegenerative diseases, including dementias. Changes in glucose metabolism precede those seen on structural MRI. Reduction in glucose metabolism and atrophy have been suggested to represent consecutive changes of neurodegeneration and are linked to specific cognitive disorders (e.g. dysexecutive syndrome, memory impairment, visuospatial deficits etc.). Advances in statistical analysis of FDG-PET images enabling a network analysis broadened our understanding of neurodegenerative brain processes. A specific cognitive pattern related to PD was identified by applying voxel-based network modeling approach. It was characterized by hypometabolism in the frontal and parietal association areas and relative increases in the cerebellar vermis and dentate nuclei. This pattern correlated significantly with patients’ cognitive skills. A topographically similar pattern was identified using resting-state functional MRI data. Specific metabolic brain changes were observed also in patients with Lewy body dementia as well as in a prodromal α-synucleinopathy: REM sleep behavior disorder. Metabolic brain imaging with FDG-PET is a reliable biomarker of neurodegenerative brain diseases, precisely reflecting their topographic distribution, stage and functional impact.